Efficacy of Bilateral Mental Nerve Block with Bupivacaine for Postoperative Pain Control in Mandibular Parasymphysis Fractures - Ali Hossein Mesgarzadeh; Hosein Afsari; Sohrab Pourkhamne; Mohamadreza Shahamfar (Tabriz University of Medical Sciences, 2014)
Background and aims. Postoperative pain control is extremely important for both patients and surgeons; in this context, long-acting local anesthesia can play an important role after open reduction of maxillofacial fractures. The purpose of this study was to evaluate the effect of bilateral mental nerve block with bupivacaine on postoperative pain control in mandibu-lar symphyseal fractures. Materials and methods. Fifty patients with pure mandibular symphyseal fractures were studied in two control and study groups. In contrast to the control group, the study group received bilateral mental nerve block with bupivacaine postopera-tively. Patients were examined in relation to pain severity and opioid analgesic drug need sequences. Results. The study group needed significantly less opioid than the control group (P<0.01, U=141). The control and study groups were different in first opioid administration time. The control and study groups received first opioid dose in 0-2 and 2-4 hours, respectively. Conclusion. Bilateral mental nerve blocks with bupivacaine can reduce opioid analgesic need and it has a positive effect on postoperative pain control in mandibular symphyseal fractures.